The Effect Ratio of Stabilizer and Concentration of Egg Yolk on The Quality of Reduced Fat Mayonnaise - Christian Aditya Hutapea; Herla Rusmarilin; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of this research was to find the the best ratio of arabic gum and CMC, with the concentration of egg yolk in producing reduced fat mayonnaise with the best characteristic of physcochemical and sensory quality that can be accepted by consumers. The research was using completely randomized design with two factors, i.e the ratio of arabic gum and CMC used were 1:4; 2:3; 3:2; and 4:1, and egg yolk was added with four concentration 5%, 7%, 9%, and 11%. The parameters analyzed were moisture content, fat content, protein content, pH value, viscosity, organoleptic value of flavor, taste, and texture. The results showed that the interaction between arabic gum and CMC with yolk concentration had highly significant effect (P<0,01) on viscosity. The reduced fat mayonnaise with the best quality based on sensory characteristic and viscosity value was the treatment with the ratio of arabic gum and CMC of 1:4 (G1) and 11% (Y4) egg yolk. The best quality of reduced fat mayonnaise had 6,75x103 CFU/g of total microbes which was lower than the maximum permissible total microbes standard (1x104 CFU/g). Keywords : Arabic gum, CMC, Egg yolk, Mayonnaise